The relationship between the leader empowering behaviors and work engagement: the role of psychological empowerment as a mediating variable - Razieh Hashemi; Amir Sadeghi; Ghodratollah Roshanaei; Zahra Purfarzad (BMC Nursing)
Abstract Background The nurse managers need to understand various leadership styles in order to support their staff and cultivate a work environment that enhances the psychological empowerment and work engagement of nurses. This research aimed to investigate the correlation between leader empowering behaviors, psychological empowerment, and work engagement in Iranian nurses. Additionally, the study looked at the role of psychological empowerment as a mediator in the connection between leader empowering behaviors and work engagement. Methods During the period from September 2021 to February 2022, a research study with descriptive, cross-sectional, and correlational design was carried out. A sample of 198 nurses was obtained using a stratified proportional random sampling approach. The data collection tools included a demographic information, Leader Empowering Behaviors Scale (LEBS), Spreitzer’s Psychological Empowerment Scale, and Utrecht Work Engagement Scale-9 (UWES-9). The data was analyzed using descriptive statistics, Pearson correlation analysis, linear regression analysis, and structural equation model (SEM). Analysis of the data was performed using SPSS ver24 and AMOS ver24. The significance level considered for the study was < 0.05. Results The average scores for leader empowering behaviors, psychological empowerment, and work engagement were 4.94, 5.64, and 3.94, respectively. According to the results, most nurses perceived high levels of leader empowering behaviors and psychological empowerment, while perceiving a moderate level of work engagement. Leader empowering behaviors had a positive and significant association with psychological empowerment (p < 0.001; β = 0.557; R2 = 0.307), and work engagement (p = 0.001; β = 0.245; R2 = 0.055). Also, psychological empowerment exhibited a positive and significant connection with work engagement (p < 0.001; β = 0.470; R2 = 0.217). Psychological empowerment was identified as mediating the relationship between leader empowering behaviors and work engagement (p = 0.001; R2 = 0.178). Conclusion Nursing managers can provide the grounds to enhance work engagement of nurses via leader empowering behaviors and attempts for improving psychological empowerment.